The effects of various surface treatments on the shear bond strengths of stainless steel brackets to artificially-aged composite restorations - Eslamian Ladan; Borzabadi-Farahani Ali; Mousavi Nasin; Ghasemi Amir (Sciendo, 2011)
Objective: To compare the shear bond strengths (SBS) of stainless steel brackets bonded to artificially-aged composite restorations after different surface treatments.